Response Conversion for Improving Comparability of International Physical Activity Data - Hopman-Rock, Marijke; Dusseldorp, Elise; Chorus, Astrid; Jacobusse, Gert; Rütten, Alfred; van Buuren, Stef (Journal of physical activity and health, 2012)
Background: Many questionnaires for measuring physical activity (PA) exist. This complicates the comparison of outcomes. Methods: In 8 European countries, PA was measured in random samples of 600 persons, using the IPAQ as a ‘bridge’ to historical sets of country-speci c questions. We assume that a unidimensional scale of PA ability exists on which items and respondents can be placed, irrespective of country, culture, background factors, or measurement instrument. Response Conversion (RC) based on Item Response Theory (IRT) was used to estimate such a common PA scale, to compare PA levels between countries, and to create a conver- sion key. Comparisons were made with Eurobarometer (IPAQ) data. Results: Appropriateness of IRT was supported by the existence of a strong rst dimension established by principal component analysis. The IRT analysis resulted in 1 common PA scale with a reasonable t and face validity. However, evidence for cultural bias (Differential Item Functioning, DIF) was found in all IPAQ items. This result made actual comparison between countries dif cult. Conclusions: Response Conversion can improve comparability in the eld of PA. RC needs common items that are culturally unbiased. Wide-scale use of RC awaits measures that are more culturally invariant (such as international accelerometer data).
Keywords: item response theory; cultural bias; differential item functioning; IPAQ